Induction of Human Immunodeficiency Virus Type 1 (HIV-1)-Specific T-Cell Responses in HIV Vaccine Trial Participants Who Subsequently Acquire HIV-1 Infection - Horton, Helen (American Society for Microbiology, 2006)
Candidate human immunodeficiency virus type 1 (HIV-1) vaccines designed to elicit T-cell immunity in HIV-1-uninfected persons are under investigation in phase I to III clinical trials. Little is known about how these vaccines impact the immunologic response postinfection in persons who break through despite vaccination. Here, we describe the first comprehensive characterization of HIV-specific T-cell immunity in vaccine study participants following breakthrough HIV-1 infection in comparison to 16 nonvaccinated subjects with primary HIV-1 infection. Whereas none of the 16 breakthrough infections possessed vaccine-induced HIV-1-specific T-cell responses preinfection, 85% of vaccinees and 86% of nonvaccinees with primary HIV-1 infection developed HIV-specific T-cell responses postinfection. Breakthrough subjects' T cells recognized 43 unique HIV-1 T-cell epitopes, of which 8 are newly described, and 25% were present in the vaccine. The frequencies of gamma interferon (IFN-γ)-secreting cells recognizing epitopes within gene products that were and were not encoded by the vaccine were not different (P = 0.64), which suggests that responses were not anamnestic. Epitopes within Nef and Gag proteins were the most commonly recognized in both vaccinated and nonvaccinated infected subjects. One individual controlled viral replication without antiretroviral therapy and, notably, mounted a novel HIV-specific HLA-C14-restricted Gag LYNTVATL-specific T-cell response. Longitudinally, HIV-specific T cells in this individual were able to secrete IFN-γ and tumor necrosis factor alpha, as well as proliferate and degranulate in response to their cognate antigenic peptides up to 5 years postinfection. In conclusion, a vaccinee's ability to mount an HIV-specific T-cell response postinfection is not compromised by previous immunization, since the CD8(+) T-cell responses postinfection are similar to those seen in vaccine-naïve individuals. Finding an individual who is controlling infection highlights the importance of comprehensive studies of breakthrough infections in vaccine trials to determine whether host genetics/immune responses and/or viral characteristics are responsible for controlling viral replication.